Modified soy protein based adhesives and their physicochemical properties - Qi, Guangyan (Kansas State University, 2013)
Soy protein is one of the most promising bio-degradable adhesives, with great potential as alternatives synthetic petroleum based adhesives for wood composite industries. However, its intrinsic drawbacks such as low water resistance, high viscosity, and short shelf life still limit its broad application. In this research, soy protein was further modified and characterized to improve adhesion properties, flow-ability, water resistance, and long shelf life, which could facilitate the industrialization of soy protein based adhesives. In this study, we exploited the in situ sodium bisulfite (NaHSO3) modification on soy protein in soy flour-water extracts, and then the modified soy protein was obtained through acid precipitation. First, different concentrations of NaHSO3 were used to modify soy flour slurry, then glycinin-rich and β-conglycinin-rich fractions were precipitated at pH 5.4 (SP 5.4) and pH 4.5 (SP 4.5), respectively. Unmodified sample SP 5.4 and SP 4.5 showed clay-like properties and viscoelastic properties, respectively; whereas with addition of NaHSO3 in range of 2-8 g/L, both SP 5.4 and SP 4.5 had the viscous cohesive phase with good handability and flow-ability. The overall adhesion performance of SP 4.5 was better than SP 5.4; the wet strength of these two fractions was in the range of 2.5-3.2 MPa compared to 1.6 MPa of control soy protein isolate. Then soy protein with various β-conglycinin/glycinin (7S/11S) ratios were extracted from soy flour slurry and characterized for adhesion properties based on the different solubility of 7S and 11S globulins. Seven glycinin-rich soy protein fractions and six β- conglycinin-rich soy protein fractions were obtained. According to the morphology, viscosity, and particle size results, we proposed that proper protein-protein interaction, hydration capacity (glycinin-rich fractions), and certain 7S/11S ratios (β-conglycinin-rich fractions) in modified soy protein are crucial to continuous protein phase formation. The viscous cohesive samples were stable for up to several months without phase separation at room temperature, with the wet adhesion strength of 2.0-2.8 MPa. The soy protein modified with NaHSO3 showed good compatibility with commercial glues applied on plywood and paper labeling fields. The modified soy protein made some functional groups, carboxylic (-COOH), hydroxyl (-OH) and amino groups (-NH2) available, which cross-linked with hydroxymethyl groups (-CH2-OH) from urea formaldehyde (UF) wood glue. The modified soy protein (MSP) with pH 4.8 also acted as an acidic catalyst for the self-polymerization of UF based resin. The wet adhesion strength of MSP/UF blends (40/60) was 6.4 MPa with 100% wood cohesive failure, as compared to 4.66 MPa of UF. As to the paper labeling application, peel strength of MSP on glass substrate increased rapidly, with curing time much shorter than commercial polyvinyl acetate based adhesives (PVAc). And the MSP/ PVAc blends showed shorter curing time, higher water resistance and lower viscosity than pure PVAc. Chemical modification could also enhance the adhesion strength of MSP. 2-octen-1- ylsuccinic anhydride (OSA) was proved to be grafted on soy protein through reaction between amine, hydroxyl groups of protein and anhydride groups. The oily nature and hydrophobic long alkyl chains of OSA mainly contributed to the significant water resistance improvement of MSP.
Keywords: Soy protein based adhesives; Chemical modification; Biodegradable; Reducing agent; Agriculture, General (0473)